Self-Correcting Mechanisms in Public Procurement: Why Award and Contract Should be Separated - Dieter Bös; Martin Kolmar (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
In public procurement a temporal separation of award and actual contracting can frequently be observed. In this paper we give an explanation for this institutional setting. For incomplete procurement contracts we show that such a separation may increase efficiency. We show that efficiency can be increased by post-award, pre-contract negotiations between the award-winning seller and one of the `losing' sellers. Surprisingly, the efficiency gains can be higher if the award is given to a seller with a lower reputation for quality instead of to a seller with higher reputation. Under certain conditions post-award, pre-contract rent-seeking activities also increase efficiency. This is always the case if the procurement agency is corrupt, but may also occur in the case of lobbying.
Keywords: D23; H57; L51; 330; Procurement; Incomplete contracts; lobbying; corruption